Lettres de pharaons aux derniers rois d’Ugarit - Lipiński, Edward (Anabasis. Studia Classica et Orientalia, 2017)
Among the Akkadian tablets found at Ugarit in 1994 and published in 2016, there are two letters sent from Egypt to the king of Ugarit. One of these letters, sent by Ramesses III to ‘Ammurapi, the last king of Ugarit, offers a chronological reference, probably after 1175 B.C. Some drafts of Ugaritic letters addressed to the pharaoh show that the ruler of Ugarit presented himself as a tributary, what shows that this submissive attitude goes back to some periods of the reigns of Ramesses II and of Merneptah, although Ugarit appears in other documents as a vassal state of the Hittite Empire. Periods of famine in the Levant may explain this ambivalent situation to some extent, but a relation of Ugarit with the Hittites and with Egypt in the later 13th and the early 12th century B.C. should be conceived in a subtle way.